Climate-Resilient Agriculture in The Philippines: Climate Risk Profile, Luzon - Giles, James; Macandog, Paula Beatrice; Nowak, Andreea C.; Pablo, Janet; Sebiano Jr, Ben; Palao, Leo K.; Balanza, Jane Girly C.; Hildebrand, Jack; Grosjean, Godefroy (2019)
The Luzon Climate Risk Profile is organized into six sections, each reflecting an essential analytical step in understanding current and potential adaptation options in key local agricultural value chains. The document first offers an overview of agricultural commodities that are crucial for food security and livelihoods in the Philippines, and describes major challenges to agricultural sector development in the island group. Next, it identifies the main climatic hazards based on analysis of historical climate data and climate projections including typhoons and drought. The profile continues with an analysis of vulnerabilities and risks posed by the hazards toward key commodities through crop suitability mapping. Based on these vulnerabilities, we discuss current and potential on farm adaptation options and off-farm services. The text also provides snapshots of the enabling policy, institutional, and governance context for adoption of resilience-building strategies. Finally, pathways for strengthening institutional capacity to address climate risks are presented.